Electrical Properties at Grain Boundaries Influenced by Cr3+ Diffusion in SnO2.ZnO.Nb2O5-Films Varistor Prepared by Electrophoresis Deposition - Lustosa, Glauco Meireles Mascarenhas Morandi [UNESP]; Costa, João Paulo C.; Perazolli, Leinig Antonio [UNESP]; Zaghete, Maria Aparecida [UNESP] (Springer Nature, 2014)
SnO2-based varistors are strong candidates to replace the ZnO-based varistors due to ordering fewer additives to improve its electrical behavior as well as by showing similar nonlinear characteristics of ZnO varistors. In this work, SnO2-nanoparticles based-varistors with addition of 1.0 %mol of ZnO and 0.05 %mol of Nb2O5 were synthesized by chemical route. SnO2.ZnO.Nb2O5-films with 5 μm of thickness were obtained by electrophoretic deposition (EPD) of the nanoparticles on Si/Pt substrate from alcoholic suspension of SnO2-based powder. The sintering step was carried out in a microwave oven at 1000 °C for 40 minutes. Then, Cr3+ ions were deposited on the films surface by EPD after the sintering step. Each sample was submitted to different thermal treatments to improve the varistor behavior by diffusion of ions in the samples. The films showed a nonlinear coefficient (α) greater than 9, breakdown voltage (VR) around 60 V, low leakage current (IF ≈ 10-6 A), height potential barrier above 0.5 eV and grain boundary resistivity upward of 107 Ω.cm.
Keywords: Electrical properties; Grain boundaries; Sn